The stability and number of nucleating interactions determine DNA hybridisation rates in the absence of secondary structure - Ouldridge,T; Hertel,S; Spinney,R; Xu,S; Morris,R; Lee,L (Nucleic Acids Research, 2022)
The kinetics of DNA hybridisation are fundamental to biological processes and DNA-based technologies.However, the precise physical mechanisms that determine why different DNA sequences hybridise at differentrates are not well understood. Secondary structure is one predictable factor that influences hybridisation ratesbut is not sufficient on its own to fully explain the observed sequence-dependent variance. In this context, wemeasured hybridisation rates of 43 different DNA sequences that are not predicted to form secondarystructure and present a parsimonious physically justified model to quantify our observations. Accounting onlyfor the combinatorics of complementary nucleating interactions and their sequence-dependent stability, themodel achieves good correlation with experiment with only two free parameters. Our results indicate thatgreater repetition of Watson-Crick pairs increases the number of initial states able to proceed to fullhybridisation, with the stability of those pairings dictating the likelihood of such progression, thus providingnew insight into the physical factors underpinning DNA hybridisation rates.